PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN YANG DIMODERASI BUDAYA ORGANISASI BANK MANDIRI KANTOR CABANG TERNATE - Waton Ruhiyat; Tristiana Rijanti (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to explorfe the dynamics of relationships between work motivation influences and career employee performance, by integrating the role of organizational culture as a moderating factor in the Bank Mandiri Ternate Branch Office enviroment. The entire population encompasses 100 employees of Bank Mandiri Ternate Branch Office, with sample determination based on permanent employee criteria and minimum 1 years of experience, yielding 80 respondents. The analytical approach utilized SPSS software version 23.0 with moderated regression techniques to test the proposed hypotheses. Empirical findings reveal that work motivation variables demonstrate a significant negative relationship with employee performance variables (coefficient β= -1,621; significance level p=0,023). Conversely, career development variables exhibit highly significant positive contributions to employee productivity (coefficient β=2,525; significance level p=0,001) the first moderation effect analysis shows that organizational culture strengthens the correlation between work motivation and employee performance. Meanwhile, the second moderation effect on the relathionsip between career development and employee performance demonstrates an opposite pattern with a negative coefficent value of -0,420 and significance p= 0,005. Keywords: work motivation, career development, employee performance, and organizational culture